Customized fault management system for low voltage (LV) distribution automation system. - Ahmed, Musse Mohamud; Soo, Wai Lian; Hanafiah , Mohd Ariff; Ab. Ghani, Mohd Ruddin (Intech, 2010)
1. Introduction Supply disruption such as overloading will cause interruptions of electricity supply to customers. The technicians have to manually locate the fault point and this tedious work may last for extended periods of time. The other reasons are the lack of use of efficient tools for operational planning and advanced methodology for quick detection of fault, isolation of the faulty section and service restoration. Currently, fault detection, isolation and service restoration takes a long time causing the interruption of supply for a longer duration.